Do, or do not. There is no try, Yoda.
In simple terms, the limit of a sequence {zₙ} is the value “z” that the terms of the sequence get arbitrarily close to as n (the index of the terms) becomes larger and larger (approaches infinity).
Formal Definition: Let {zₙ} be a sequence of complex numbers, and let z be a complex number. We say that the sequence {zₙ} converges to z, denoted or written as {zₙ} → z as n → ∞, if for every positive real number ε (epsilon: represents an arbitrary small positive number and defines how close the term zₙ need to be to the limit z, that is, the radius of a small circle, disk, or neighborhood centered at z), there exists a natural number N (a point in the sequence beyond which all subsequent terms fall into line, meaning they are all within the circle centered at z of radius ε) such that for all natural numbers n greater than or equal to N, the distance between zₙ and z is less than ε: ∀ε > 0, ∃N ∈ ℕ : (such that) ∀n ≥ N (“for all n greater than or equal to N”), |zn - z| < ε.
In other words, no matter how small you choose ε (i.e., no matter how close you want the terms to be close to the limit, how small the disk or circle around z with radius ε is), you can always find a point in the sequence (N) such that all terms after that point lie inside this circle or are within a distance of ε from the limit z.
Example. Consider the sequence zₙ = (1 + i)/n, $\lim_{n \to \infty} \frac{1+i}{n} = 0$
∀ε > 0, ∃N ∈ ℕ, N = $\frac{2\sqrt{2}}{ε}$ : ∀n ≥ N, |zn - z| < ε.
|zn - z| = |(1 + i)/n| = |$\frac{1+i}{n}| = \frac{|1+i|}{n} = \frac{\sqrt{2}}{n} ≤ \frac{\sqrt{2}}{N} = \frac{ε}{2} < ε$
Theorem. Convergence of Complex Sequences and Real/Imaginary Parts A sequence of complex numbers {zₙ} converges to a complex number z if and only if the sequences of their real parts {xₙ} and imaginary parts {yₙ} converge to the real and imaginary parts of z, respectively. {zₙ} → z, where zₙ = xₙ + iyₙ ∀n, z = x + iy, if and only if {xₙ} → x and {yₙ} → y
Proof:
(=>)
Suppose $\lim_{n \to \infty} z_n = z$, for any ε > 0, there exists an N such that for all n ≥ N, |zₙ - z| < ε.
|zₙ - z| = |(xₙ - x) + i(yₙ - y)| = $\sqrt{((xₙ - x)² + (yₙ - y)²)}< ε => (xₙ - x)² < ε² \text{~and~} (yₙ - y)² < ε²$. Taking the square root, we get |xₙ - x| < ε and |yₙ - y| < ε.
This shows that for any ε > 0, there exists an N such that for all n ≥ N, |xₙ - x| < ε and |yₙ - y| < ε. Therefore, $\lim_{n \to \infty} x_n = x \text{~and~} \lim_{n \to \infty} y_n = y$.
(<==)
Assume $\lim_{n \to \infty} x_n = x \text{~and~} \lim_{n \to \infty} y_n = y$. This means for any ε > 0, there exist N₁ and N₂ such that for all n ≥ N₁, |xₙ - x| < ε/√2, and for all n ≥ N₂, |yₙ - y| < ε/√2.
Let N = max(N₁, N₂). Then for all n ≥ N, both inequalities hold, so now consider |zₙ - z| = $\sqrt{(xₙ - x)² + (yₙ - y)²} < \sqrt{\frac{ε²}{2} + \frac{ε²}{2}} = \sqrt{ε²} = ε$.
A Cauchy sequence is a sequence in which the terms become arbitrarily close to each other as the sequence progresses.
Formally, a complex sequence {zₙ} is called a Cauchy sequence if for every positive real number ε (indicating how close the terms should be), there exists a natural number N (indicating the point in the sequence after which the terms are guaranteed to be as close as required) such that for all natural numbers n and m greater than or equal to N, the distance between zₙ and zₘ is less than ε: ∀ε > 0, ∃N ∈ ℕ : (such that) ∀n, m ≥ N, |zₙ - zₘ| < ε.
Definition. A metric space is a set M equipped with a distance or metric function d: M × M → ℝ that defines a notion or construct of distance between any two points in the set. Basically, it satisfies the following four axioms. ∀x, y, z ∈ M (for any three points in the set):
Common Examples:
Definition: A metric space (or a subset of a metric space) is said to be complete if every Cauchy sequence in that space (or subset) converges to a limit that is also within that space (or subset).
Consider the set of rational numbers ℚ (with the usual absolute value as the metric). The sequence defined by the decimal approximations of √2 (1, 1.4, 1.41, 1.414, …) is a Cauchy sequence in ℚ. However, the limit of this sequence is √2, which is not a rational number (√2 ∉ ℚ). Therefore, the set of rational numbers ℚ is not complete.
On the other hand, the set of real numbers ℝ (with the usual absolute value as the metric) is complete. Any Cauchy sequence of real numbers converges to a limit that is also a real number. Similarly, the complex plane ℂ is complete.
In summary: Completeness is a property of a metric space (or a subset thereof) that guarantees that Cauchy sequences within the space have limits that are also within the space.
Th. The complex plane is complete.
Proof.
Let {zₙ} be a Cauchy sequence in ℂ. This means that for any ε > 0, there exists an N ∈ ℕ such that for all n, m ≥ N, |zₙ - zₘ| < ε.
Express the complex numbers in terms of their real and imaginary parts: Let zₙ = xₙ + iyₙ and zₘ = xₘ + iyₘ, where xₙ, yₙ, xₘ, and yₘ are real numbers.
Rewrite the Cauchy condition: |zₙ - zₘ| = |(xₙ - xₘ) + i(yₙ - yₘ)| = $\sqrt{(xₙ - xₘ)² + (yₙ - yₘ)²}$ < ε
Since the square root of a sum of squares is less than ε, each square must also be less than ε²: (xₙ - xₘ)² < ε² and (yₙ - yₘ)² < ε²
Taking the square root of both sides gives: |xₙ - xₘ| < ε and |yₙ - yₘ| < ε
Cauchy sequences of real numbers: This shows that {xₙ} and {yₙ} are Cauchy sequences of real numbers. Since the real numbers ℝ are complete, every Cauchy sequence of real numbers converges to a real number. Therefore, there exist real numbers x and y such that: $\lim_{n \to \infty} xₙ = x \text{~and~} \lim_{n \to \infty} yₙ = y$
Next, we construct the complex limit: Let z = x + iy and aim to demonstrate that {zₙ} converges to z: We want to show that for any ε > 0, there exists an N such that for all n ≥ N, |zₙ - z| < ε.
|zₙ - z| = |(xₙ - x) + i(yₙ - y)| = $\sqrt{(xₙ - x)² + (yₙ - y)²}$
Since $\lim_{n \to \infty} xₙ = x \text{~and~} \lim_{n \to \infty} yₙ = y$, for any ε > 0, there exist N₁ and N₂ such that for all n ≥ N₁, |xₙ - x| < ε/√2, and for all n ≥ N₂, |yₙ - y| < ε/√2.
Let N = max(N₁, N₂). Then for all n ≥ N:
|zₙ - z| = $\sqrt{(xₙ - x)² + (yₙ - y)²} < \sqrt{(ε/√2)² + (ε/√2)²} = \sqrt{ε²/2 + ε²/2}$ = ε
Conclusion: We have shown that for any ε > 0, there exists an N such that for all n ≥ N, |zₙ - z| < ε. This means that the sequence {zₙ} converges to the complex number z = x + iy.
Proposition. We assume a ∈ ℂ, and f is a complex function with $\lim_{z \to a} f(z) = L_1$ and $\lim_{z \to a} f(z) = L_2$ then L1 = L2, in other words, limits are unique.
Proof.
Let ε > 0, there exists δ₁ and δ₂ for which 0 < | z -a | < δ₁ implies | f(z) - L₁ | < ε/2, and 0 < | z -a | < δ₂ implies | f(z) - L₂ | < ε/2
Let δ = min{δ₁, δ₂} and suppose 0 < | x -a | < δ ≤ δ₁, δ₂, then:
| L₁ - L₂ | = | L₁ - f(z) + f(z) - L₂ | ≤ | L₁ - f(z) | + | f(z) - L₂ | < ε/2 + ε/2 = ε. Thus, | L₁ - L₂ | < ε for arbitrary ε, that implies | L₁ - L₂ | = 0 ➞ L₁ = L₂.
Proposition. Limit of identity function, $\lim_{z \to a} z = a$.
Let ε > 0, there exists δ (choose δ = ε) for which 0 < | z -a | < δ = ε, obviously implies | z - a | < ε
Proposition. Limit of constant function, $\lim_{z \to a} c = c$.
Let ε > 0, there exists δ (choose δ = 42, the answer to the meaning of life, the universe and everything else) for which 0 < | z -a | < δ, obviously implies | c - c | = 0 < ε
Proposition. We assume a ∈ ℂ, and f and g are complex function with $\lim_{z \to a} f(z) = L_f$ and $\lim_{z \to a} g(z) = L_g$ then $\lim_{z \to a} f(z)+g(z) = L_f+L_g$.
Proof.
Let ε > 0, there exists δ₁ and δ₂ for which 0 < | z -a | < δ₁ implies | f(z) - L₁ | < ε/2, and 0 < | z -a | < δ₂ implies | g(z) - L₂ | < ε/2
Let δ = min{δ₁, δ₂} and suppose 0 < | x -a | < δ ≤ δ₁, δ₂, then:
$|f(z)+g(z) - (L_f+L_g)| = |f(z) - L_f + g(z) - L_g| ≤ | f(z) - L_f | + | g(z) - L_g | < ε/2 + ε/2 = ε $
Proposition. Homogeneity of the limit. Suppose c ∈ ℂ and $\lim_{z \to a} f(z) = L$, then $\lim_{z \to a} cf(z) = c\lim_{z \to a} f(z)$
Assume c ≠ 0. Let ε > 0, there exists δ for which 0 < | z -a | < δ implies | f(z) - L | < ε/|c|
| cf(z) - cL | = |c|∙| f(z) - L | < |c| ∙ ε/|c| = ε.
If c = 0, | 0f(z) - 0L | = 0 < ε for all z ∈ dom(f).
Proposition. Limit of linear combination of convert functions. Suppose a ∈ ℂ, and $\lim_{z \to a} f_i(z) = L_i$. Then, $\lim_{z \to a} (cf_1+cf_2 + … + cf_n)(z) = c_1\lim_{z \to a} f_1(z) + c_2\lim_{z \to a} f_2(z) + … + c_n\lim_{z \to a} f_n(z) $
Proof. We will prove it by induction on n.
n = 1. It was previously proved. Homogeneity of the limit, $\lim_{z \to a} cf(z) = c\lim_{z \to a} f(z)$.
Inductively, suppose the claim is true for some n ∈ ℕ, consider the limit of the linear combination of $\lim_{z \to a} (cf_1+cf_2 + … + cf_{n+1})(z) = \lim_{z \to a} (cf_1+cf_2 + … + cf_{n})(z)+ \lim_{z \to a} cf_n(z) = c_1\lim_{z \to a} f_1(z) + c_2\lim_{z \to a} f_2(z) + … + c_n\lim_{z \to a} f_n(z) + c_{n+1}\lim_{z \to a} f_{n+1}(z)$
Proposition. Limit of products is product of limits. We assume a ∈ ℂ, and f and g are complex function with $\lim_{z \to a} f(z) = L_f$ and $\lim_{z \to a} g(z) = L_g$ then $\lim_{z \to a} f(z)·g(z) = L_f·L_g$.
Proof
$|f(z)·g(z) - L_f·L_g| = |f(z)g(z) -L_fg(z) + L_fg(z) - L_fL_g| ≤ |f(z) -L_f||g(z)| + |L_f||g(z) - L_g|$
Let ε > 0, there exists δ₁ for which 0 < | z -a | < δ₁ implies $| f(z) - L_f | < \frac{ε}{2(1+|L_g|)}$. Analogously, there exists δ₂ for which 0 < | z -a | < δ₂ implies $| g(z) - L_g | < \frac{ε}{2(1+|L_f|)}$. Besides, there exists δ₃ for which 0 < | z -a | < δ₃ implies $| g(z) - L_g | < 1 ⇒ | g(z) | = | g(z) - L_g + L_g | ≤ | g(z) - L_g | + | L_g | < 1 + | L_g |$
Let δ = min{ δ₁, δ₂, δ₃}, 0 < | z -a | < δ:
$|f(z)·g(z) - L_f·L_g| ≤ |f(z) -L_f||g(z)| + |L_f||g(z) - L_g| < \frac{ε}{2(1+|L_g|)}(1 + | L_g |) + |L_f|\frac{ε}{2(1+|L_f|)} < \frac{ε}{2}+\frac{ε}{2} = ε$ because $\frac{|L_f|}{1+|L_f|} < 1$
Proposition. Power function limit. Let a ∈ ℝ and n ∈ ℕ, $\lim_{x \to a} z^n = a^n$
Proof by induction on n.
n = 0, $\lim_{x \to a} 1 = 1$. It has already been proved by Proposition. Limit of constant function, $\lim_{z \to a} c = c$ where c = 1.
Inductively, suppose that $\lim_{x \to a} z^n = a^n$, then:
$\lim_{x \to a} z^{n+1}=\lim_{x \to a} z^n·z =[\text{By product of limit theorem}] (\lim_{x \to a} z^n)·(\lim_{x \to a} z) =[\text{By induction and limit of identity function}] a^n·a = a^{n+1}.$
Proposition. Polynomial function limit. Suppose $c_0, c_1, c_2, ···, c_n$ ∈ ℝ, and p(z) = $c_0 + c_1z + c_2z² + ··· + c_nz^n$, then $\lim_{x \to a}p(z) = p(a)$ (direct consequence of previous results).
Proposition. Reciprocal function limit. Let a ∈ ℝ, a ≠ 0, and n ∈ ℕ, $\lim_{z \to a} \frac{1}{z} = \frac{1}{a}$
Proof.
$\frac{1}{z} = \frac{x-iy}{x²+y²} = \frac{x}{x²+y²} + \frac{-iy}{x²+y²} = u(z) + iv(z)$.
Let $a = x_0 + iy_0$, a ≠ 0, then since the functions are continuous at a (Calculus multivariable), $x_0²+y_0² > 0, \lim_{z \to a}u(z) = \frac{x_0}{x_0²+y_0²}, \lim_{z \to a}u(z) = \frac{x_0}{x_0²+y_0²}, \lim_{z \to a}v(z) = \frac{-y_0}{x_0²+y_0²}$
$\lim_{z \to a} \frac{1}{z} = \frac{x_0}{x_0²+y_0²} + i\frac{-y_0}{x_0²+y_0²} = \frac{x_0-iy_0}{x_0²+y_0²} = \frac{1}{a}$
Proposition. Limit of quotient is quotient of limits. We assume a ∈ ℂ, and f and g are complex function with $\lim_{z \to a} f(z) = L_f$ and $\lim_{z \to a} g(z) = L_g$ with Lg ≠ 0 then $\lim_{z \to a} \frac{f(z)}{g(z)} = \frac{L_f}{L_g}$.
If F : U ⊆ ℝn ➞ ℝn is a function, and a ∈ U is an interior point of U for which the limit $\lim_{h \to 0} \frac{F(a+h)-F(a)-L(h)}{||h||}$ exists where L(h) = DFa is a linear transformation, then we say F is differentiable at a with derivative Dfa: ℝn ➞ ℝn
The Derivative DFₐ: The derivative DFₐ is a linear transformation, not just a value. It’s often represented by a matrix (the Jacobian matrix) when working with functions from ℝⁿ to ℝᵐ.
Let ej = (0, 0, ···1j···, 0), (ej)i defined as
$(e_j)_i = \begin{cases} 0, i ≠ j \\ 1, i = j \end{cases}$
The identity matrix I = [e1, e2, ···, en]
Definition. Let F : U ⊆ ℝⁿ → ℝᵐ be a function, where U is an open set in ℝⁿ. Let a = (a₁, a₂, …, aₙ) be a point in U. Let eⱼ be the j-th standard basis vector in ℝⁿ. The partial derivative of F with respect to xⱼ at the point a, denoted by $\frac{∂F}{∂x_j}$ is defined as $\frac{∂F}{∂x_j}(a) = \lim_{t \to 0} [\frac{F(a+te_j)-F(a)}{t}]$ where
Example. F(s, t) = (s²+t³, 2st, s + 3t), F : ℝ2 ➞ ℝ3
$\frac{∂F}{∂s} = (\begin{smallmatrix}2s\\ 2t\\ 1\end{smallmatrix}), \frac{∂F}{∂t} = (\begin{smallmatrix}3t²\\ 2s\\ 3\end{smallmatrix})$.
The Jacobian matrix JF (or the differential dF(s,t)) is formed by placing these column vectors side by side: $J_F =[\frac{∂F}{∂s}|\frac{∂F}{∂t}] = [dF_{s, t}] = (\begin{smallmatrix}2s & 3t²\\ 2t & 2s\\ 1 & 3\end{smallmatrix})$
The definition of the partial derivative is the limit of the difference quotient as the change in the corresponding variable approaches zero.
Definition. Let F : U ⊆ ℝⁿ → ℝᵐ be a function, where U is an open set in ℝⁿ. Suppose F can be written in terms of its component functions: F(x) = (F₁(x), F₂(x), …, Fₘ(x)) where each Fᵢ : U ⊆ ℝⁿ → ℝ is a scalar-valued function.
The Jacobian matrix of F at a point a ∈ U, denoted by JF(a), is an m × n matrix whose entries are the partial derivatives of the component functions: $J_F =[\text{the Jacobian matrix can be written in terms of column vectors (partial derivatives with respect to each variable)}] [\frac{∂F}{∂x_1}|\frac{∂F}{∂x_2}| ··· |\frac{∂F}{∂x_n}] = (\begin{smallmatrix}\frac{∂F_1}{∂x_1} & \frac{∂F_1}{∂x_2} & ··· & \frac{∂F_1}{∂x_n}\\\frac{∂F_2}{∂x_1} & \frac{∂F_2}{∂x_2} & ··· & \frac{∂F_2}{∂x_n}\\· & · & · & ·\\· & · & · & ·\\· & · & · & ·\\\frac{∂F_m}{∂x_1} & \frac{∂F_m}{∂x_2} & ··· & \frac{∂F_m}{∂x_n}\end{smallmatrix}) = (\begin{smallmatrix}(∇F_1)^T\\ ··· \\ (∇F_2)^T\\ (∇F_m)^T\end{smallmatrix})$ where $(∇F_i)^T$ represents the transpose of the gradient vector of Fᵢ at a
Theorem. If F : U ⊆ ℝⁿ → ℝᵐ is differentiable at a point a ∈ U, then the differential dFₐ(h) (which is a linear transformation from ℝⁿ to ℝᵐ) can be represented by matrix multiplication using the Jacobian matrix:
dFₐ(h) = JF(a)·h where h is a vector in ℝⁿ (represented as a column vector).
The differential dFₐ is the best linear approximation of the change in F near the point a. The Jacobian matrix JF(a) is the matrix that represents this linear transformation. When you multiply the Jacobian matrix by the vector h, you get the approximate change in F corresponding to the small change h.
Examples:
Theorem. Suppose f, g: ℂ ➞ ℂ have partial derivatives which exist then:
Proof (Product rule)
Suppose f = u + iv, g = a + ib, fg = (u + iv)(a + ib) = ua -ub + i(ub +va)
Now, let’s take the partial derivatives:
∂/∂x(fg) = ∂/∂x(ua - vb) + i∂/∂x(ub + va) …
… = (∂u/∂x)a + u(∂a/∂x) - (∂v/∂x)b - v(∂b/∂x) + i[(∂u/∂x)b + u(∂b/∂x) + (∂v/∂x)a + v(∂a/∂x)] þ*|
Now, if we assume that a and b are the real and imaginary parts of a function g(z) = a(x,y) + ib(x,y), then we can use the product rule for real valued functions.
If a and b are independent of x (i.e., they are constants or functions of y only), then ∂a/∂x = 0 and ∂b/∂x = 0. In this simpler case, the expression becomes:
∂/∂x(fg) = þ*| (∂u/∂x)a - (∂v/∂x)b + i[(∂u/∂x)b + (∂v/∂x)a]
= (∂u/∂x + i∂v/∂x) (a + ib) = (∂/∂x)f g
If we consider the case where a and b are not independent of x, we can rewrite the expression as:
∂/∂x(fg) = þ*| (∂u/∂x + i∂v/∂x)(a+ib) + (u+iv)(∂a/∂x+i∂b/∂x) =[f = u + iv, g = a + ib] (∂f/∂x)g + f(∂g/∂x)
The proof of $∂_y(fg) = (∂_y(f))g + f(∂_y(g))$ is completely similar.
The differential of a function at a point $(\vec{x},\vec{y})$, denoted by $df_{(\vec{x},\vec{y})}$ is a linear transformation that best approximates the change in f for small changes in its arguments. Because our input is ($\vec{x}$, $\vec{y}$) ∈ ℝ³xℝ³, a small change around that point will be ($Δ\vec{x}$, $Δ\vec{y}$). The differential $df_{(\vec{x},\vec{y})}$ is a linear transformation in these increments $Δ\vec{x}$ and $Δ\vec{y}$.
To find the matrix (or row-vector) representation of the differential, we compute the gradient of f, treating $\vec{x} = (x_1, x_2, x_3)$ and $\vec{y} = (y_1, y_2, y_3)$ components as independents variables. Hence, f depends on six independent variables. To find the differential, we can compute the partial derivatives of f with respect to each component of $\vec{x}$ and $\vec{y}$
$\frac{∂f}{∂x_1} = y_1, \frac{∂f}{∂x_2} = y_2, \frac{∂f}{∂x_3} = y_3, \frac{∂f}{∂y_1} = x_1, \frac{∂f}{∂y_2} = x_2, \frac{∂f}{∂y_3} = x_3, ∇f(\vec{x},\vec{y}) = \Biggl(\begin{smallmatrix}y_1\\ y_2\\ y_3 \\x_1 \\x_2 \\x_3\end{smallmatrix}\Biggr)$
$[df_{(\vec{x},\vec{y})}] = ∇f(\vec{x},\vec{y})^T = [y_1, y_2,y_3,x_1,x_2,x_3]$
Notice that if we have small changes or increments in $\vec{x}$ and $\vec{y}$, denoted by $Δ\vec{x}$ = (Δx₁, Δx₂, Δx₃) and $Δ\vec{y}$ = (Δy₁, Δy₂, Δy₃), then the approximate change in f is given by: $df_{(\vec{x},\vec{y})}(Δ\vec{x}, Δ\vec{y})$ and found by taking the dot product of $∇f(\vec{x},\vec{y})$ with the increment vector: $df_{(\vec{x},\vec{y})}(Δ\vec{x}, Δ\vec{y}) = [y_1, y_2,y_3,x_1,x_2,x_3] * (Δx_1, Δx_2, Δx_3, Δy_1, Δy_2, Δy_3)^T = y_1Δx_1 + y_2Δx_2 + y_3Δx_3 + x_1Δy_1 + x_2Δy_2 + x_3 = (\vec{y}·Δ\vec{x}) + (\vec{x}·Δ\vec{y})$ where $(\vec{y}·Δ\vec{x})$ is the change contributed by $Δ\vec{x}$ while $\vec{y}$ is held fixed, and analogously $(\vec{x}·Δ\vec{y})$ is the change contributed by $Δ\vec{y}$ while $\vec{x}$ is held fixed. Thus, the total small change is $f(\vec{x}, \vec{y}) = \vec{x} · \vec{y}$ is the sum of these two small changes, and this argument perfectly aligns with our intuition about how the dot product operates.